EKSPLORASI ETNOMATEMATIK PADA KAIN RAGIDUP ULOS PADA KONSEP BANGUNAN DATAR - Basmara, Anggi; Yahfizham (Universitas Swadaya Gunung Jati., 2024)
This research aims to explore the mathematical concepts found in Ulos Ragidup fabric from an ethnomathematics perspective, focusing on the recognition and understanding of flat shapes. Through a descriptive qualitative approach and ethnographic method, data collection was carried out through direct observation, interviews with resource persons who are experts in the field of ulos weaving, and visual documentation. Data analysis was conducted by reducing, presenting, and interpreting data to identify mathematical patterns in Ulos Ragidup fabric motifs. The results showed that Ulos Ragidup fabric applies several flat building concepts, namely square, equilateral triangle, isosceles triangle, rectangle, and rhombus. The integration of ethnomathematics in Ulos Ragidup fabric motifs shows that mathematics is not only relevant in the academic context, but also in everyday life and local culture. This research is expected to contribute to the development of a more inclusive and contextualized mathematics education, as well as raising awareness of the importance of preserving cultural heritage through learning integrated with local values